Reconstruction of Public Participation in The AMDAL Licensing Process in Indonesia - Muhammad Yusuf Muda Azka; Irwan Triadi; Slamet Tri Wahyudi (International Journal of Social Science and Humanity, 2025)
The Environmental Impact Assessment (AMDAL) licensing process in Indonesia faces significant challenges regarding meaningful public participation, particularly following the implementation of the Job Creation Law (UU Cipta Kerja). Objective: This research analyzes the urgency for reconstructing public participation mechanisms in AMDAL formation and proposes ideal regulatory frameworks for enhanced community involvement in environmental decision-making processes. This normative legal research employs conceptual and statutory approaches, utilizing qualitative descriptive analysis of legal materials including primary sources (legislation and court decisions) and secondary sources (legal literature and scholarly articles). The study reveals that post-Job Creation Law implementation has significantly restricted public participation scope, limiting involvement to only directly affected communities while excluding environmental advocates and civil society organizations from AMDAL processes. The transition from AMDAL Assessment Commission to Environmental Feasibility Assessment Team has further centralized decision-making authority and reduced community representation. Reconstruction of public participation mechanisms is urgently needed to restore meaningful community involvement, implement good environmental governance principles, and ensure transparency, accountability, and inclusive stakeholder engagement in environmental impact assessment processes.